Autoantibodies to the low density lipoprotein receptor in a subject affected by severe hypercholesterolemia. - Corsini, A (1986)
We studied a 32-yr-old man with a benign paraproteinemia (IgA) affected by severe nonfamilial hypercholesterolemia. In vitro experiments demonstrated that lipoprotein-deficient serum (LPDS) from the patient inhibited the binding of low density lipoprotein (LDL) to human skin fibroblasts cultured in vitro (up to 70%) whereas LPDS from controls had no effect. Removal of IgA from the patient's serum by immunoprecipitation with mono-specific antisera abolished the inhibition of LDL binding. IgA isolated from the serum of the patient by affinity chromatography inhibited, in a dose-dependent manner, the binding of LDL to human skin fibroblasts in vitro, thus showing an IgA-mediated effect. Ligand-blotting experiments demonstrated that the paraprotein directly interacts with the LDL receptor, thus inhibiting the binding of the lipoprotein. Treatment of the receptor protein with reducing agents blocked the interaction of the antibody with the LDL receptor. From these data we speculate that this autoantibody may be responsible for the severe nonfamilial hypercholesterolemia of the patient.